2009
DOI: 10.1182/blood-2009-02-204883
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cAMP signaling inhibits DNA damage–induced apoptosis in BCP-ALL cells through abrogation of p53 accumulation

Abstract: In lymphocytes, the second messenger cyclic adenosine monophosphate (cAMP) plays a well-established antiproliferative role through inhibition of G 1 /S transition and S-phase progression. We have previously demonstrated that, during S-phase arrest, cAMP inhibits the action of S phase-specific cytotoxic compounds, leading to reduction in their apoptotic response. In this report, we provide evidence that cAMP can also inhibit the action of DNA-damaging agents independently of its effect on S phase. Elevation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
71
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 55 publications
11
71
2
Order By: Relevance
“…2). In accordance with previous findings (16,24), exposure of cells to IR in the presence of TSA or NIA increased the IR-mediated acetylation of p53. However, pretreatment of cells with both TSA and NIA substantially further enhanced the p53 acetylation induced by IR.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…2). In accordance with previous findings (16,24), exposure of cells to IR in the presence of TSA or NIA increased the IR-mediated acetylation of p53. However, pretreatment of cells with both TSA and NIA substantially further enhanced the p53 acetylation induced by IR.…”
supporting
confidence: 93%
“…Elevation of intracellular cAMP levels has an inhibitory effect on DNA damage-induced apoptosis in normal lymphoid cells as well as BCP-ALL cells (16). We have previously shown that this inhibitory effect of cAMP is mediated through its ability to abrogate the DNA damage-induced p53-HDM2 dissociation, leading to restoration of p53 degradation in DNA-damaged cells (17).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, previous studies have shown that activation of cAMP signaling inhibits DNA damage-induced apoptosis in BCP-ALL cells through abrogation of p53 accumulation and promotion of p53 and HDM2 interaction (8,16). However, PDE4C remains a putative tumor suppressor, as it has not been identified in gliomas.…”
Section: Integrated Analysis Using Methylation and Gene Expression MImentioning
confidence: 97%
“…Previous studies have shown that the expression of genes related to glioma progression include COL4A2, FOXM1, MGP, TOP2A, CENPF, IGFBP4, VEGFA, ADD3, CAMK2G, KI-67, YKL-40 and SMAD4, all of which are associated with the World Health Organization (WHO) glioma grade (4-6). Moreover, gene methylation is believed to play a crucial role in tumor progression, partially by repressing tumor suppressor genes, inhibiting their accumulation and inducing their mutation (7,8). Conversely, prognostic markers with potential clinical significance have been identified through genome-…”
Section: Introductionmentioning
confidence: 99%